The development of the rule of law in ASEAN the state and regional integration - Deinla, Imelda (Cambridge [UK] New York Cambridge University Press, 2017)
"An interdisciplinary work that comparatively studies rule of law practices and the relationship between the rule of law and regional integration, a topic largely explored in European integration. By looking at the function of the rule of law in ASEAN rather than what it 'means' measured on normative conception, the book situates the rule of law in broader institutional and political processes in the member states and in regional relations to show the motivations of member states in adopting a peculiar type of regional architecture. It asks whether forging the rule of law in the region can help build it internally for member states. The book revisits discourses on the 'spill-over' of economic integration, the impact of globalization in reshaping the state and generating new tools of the rule of law. It makes a comprehensive comparison - the European Union, Africa Union and MERCOSUR - showing the uneven pathways to rule of law in various contexts"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: ASEAN; Rule of law -- Southeast Asia; Southeast Asia -- Economic integration; Southeast Asis -- Politics and government